Multifunctional interface engineering enables efficient and stable inverted organic photovoltaics - Bowen Liu; Jian Qin; Qun Luo; Chang-Qi Ma (Nature Communications)
Compared to conventional (p-i-n) organic photovoltaics (OPVs), inverted (n-i-p) OPVs hold promise for future commercial applications due to their advantages in printing process compatibility and environment robustness. The current bottleneck lies in the efficiency and light stability, which is closely related to the defects and the photocatalytic reactivity of metal oxides transport layer. This comment summarizes the recent progress on inverted OPV and outlines potential solutions to surmount the hurdles before the technology can be put into production.